The Conquest of the Old Southwest; the romantic story of the early pioneers into Virginia, the Carolinas, Tennessee, and Kentucky, 1740-1790 - Henderson, Archibald, 1877-1963 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Conquest of the Old Southwest: The Romantic Story of the Early Pioneers" by Archibald Henderson is a historical account written in the early 20th century. The book explores the dramatic southward and westward expansion of European settlers onto the American continent during the 18th century, focusing on their struggles and triumphs as they confront both environmental challenges and indigenous populations. At the start of the book, the author emphasizes the significant sociopolitical transformations stimulated by the migration of peoples into the Old Southwest. He describes the relentless and adventurous spirit of early pioneers who ventured into the wilderness, many vividly depicted through the tale of a single family's journey. These pioneers contended with harsh conditions, conflicts with Native Americans, and the overall chaos of expanding civilization, setting the stage for a broader examination of how such movements shaped America's national character and democratic ideals. Henderson's narrative intertwines personal stories with broader historical events, indicating the complex dynamics that influenced the formation of society in the emerging American frontier. (This is an automatically generated summary.)
Release date is 2000-11-01
Dianne Bean, Robert Homa and Al Haines
Keywords: Kentucky -- History -- To 1792; Southwest, Old -- History; Tennessee -- History; Frontier and pioneer life -- Southwest, Old